2022
DOI: 10.1007/s00382-022-06591-9
|View full text |Cite|
|
Sign up to set email alerts
|

Near-term regional climate change in East Africa

Abstract: In the coming few decades, projected increases in global temperature and humidity are generally expected to exacerbate human exposure to climate extremes (e.g., humid-heat and rainfall extremes). Despite the growing risk of humid-heat stress (measured by wet-bulb temperature), it has received less attention in East Africa, where arid and semi-arid climatic conditions prevail. Moreover, no consensus has yet been reached across models regarding future changes in rainfall over this region. Here, we screen Global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…The increase in temperature and drying conditions have resulted in increased drought in many places of the Earth [7,[118][119][120][121][122][123][124]. During the last years, East Africa has experienced more recurrent, intense, and longer-lasting drought events [11,[13][14][15][16][17]119], causing damage to infrastructure, water scarcity, drying of crops, famine, and food insecurity, leading to the frequent migrations of populations [17][18][19][20][21]. Recent observations have indicated that the eastern and southeastern parts of Rwanda have been experiencing rainfall deficits, resulting in severe droughts alternated by prolonged moderated drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in temperature and drying conditions have resulted in increased drought in many places of the Earth [7,[118][119][120][121][122][123][124]. During the last years, East Africa has experienced more recurrent, intense, and longer-lasting drought events [11,[13][14][15][16][17]119], causing damage to infrastructure, water scarcity, drying of crops, famine, and food insecurity, leading to the frequent migrations of populations [17][18][19][20][21]. Recent observations have indicated that the eastern and southeastern parts of Rwanda have been experiencing rainfall deficits, resulting in severe droughts alternated by prolonged moderated drought.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent experience that the East African region has known and knows today, the impacts of climate change have not spared Rwanda [14][15][16]. The country has committed to undertake adaptation and mitigation measures to the greatest extent possible for vulnerable communities.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Both GCMs and regional climate models (RCMs) suffer from systematic biases which could be attributed to complex topography, weaknesses in parameterization schemes, coarse spatial resolutions, and atmosphere-biosphere process transitions over large water bodies (Allen et al, 2002;Cardell et al, 2019;Ayugi et al, 2020;Choi et al, 2023). East Africa, a region marked with complex topography such as mountains, the Great Rift Valley (GRV), and major inland water bodies, is a case where systematic biases present a challenge in the generation of skilful climate services for operational applications.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, for instance, climate models project drier states in the southern region and highly variable and reduced rainfall in West Africa (Kotir, 2011). However, these models lack consensus regarding future precipitation changes in the East Africa (EA) region (Choi et al, 2023). The EA region comprises the greater horn of Africa, which in the recent past has witnessed frequent droughts and persistent food shortages (Nicholson, 2014).…”
Section: Introductionmentioning
confidence: 99%